The rational project manager a thinking team's guide to getting work done - Longman, Andrew 1959- (John Wiley & Sons, 2005)
This comprehensive exploration of the project management process presents the tools, steps, and processes of project management and uncovers the critical thinking - the why - vital to project management excellence. Incorporating Kepner-Tregoe's renowned and effective problem-solving and decision-making processes, the book guides you through the core activities of project management planning, solving problems, making decisions, and assessing risk. It positions projects within an organization's 'performance environment', an understanding of which is essential for effective team performance and alignment. Offering a combination of overarching insights into organizational dynamics, as well as specific processes and practices for effective management, this is a resource no project leader - and no project team member - should be without.